A solid-state lithium-ion battery and a method for preparing the same
By introducing the ionic liquid treatment layer and negative electrode coil double-layer transfer process into solid-state lithium-ion batteries, combined with the double-steel belt press process, the problems of low assembly efficiency and low yield of sulfide all-solid-state batteries are solved, and high efficiency is achieved , stable battery assembly.
Patent Information
- Application Number
- CN202410493347.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-04-23
AI Technical Summary
The existing continuous assembly process of sulfide all-solid state batteries has problems such as low assembly efficiency, easy short circuit after high-voltage forming of the battery, and low yield.
By introducing an ionic liquid treatment layer into a solid lithium-ion battery, the transfer success rate of the electrolyte membrane is improved, and the negative electrode coil positive/back double-layer transfer electrolyte layer process is adopted, combined with the double steel belt press process, the assembly efficiency and Yield rate.
It significantly improves the yield rate and efficiency of assembly, avoids short-circuit failure of battery cells, and improves the production capacity of all-solid-state batteries.
Smart Images

Figure CN118367205B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a solid-state lithium-ion battery and a preparation method thereof. Background Art
[0002] Sulfide all-solid-state batteries use stable inorganic sulfide electrolyte powder to replace the flammable electrolyte and separator in traditional batteries, which can greatly improve the safety of the battery. At the same time, they match new positive and negative electrodes to achieve high safety at high specific energy. Compared with traditional liquid lithium-ion batteries, they have the following advantages:
[0003] (1) High safety performance. When a liquid electrolyte short-circuits, the temperature rises, ignites the electrolyte and causes an explosion. Sulfide solid electrolytes are non-flammable, non-corrosive, non-volatile, and have no leakage problems. They also overcome the lithium dendrite phenomenon, so all-solid-state batteries have extremely high safety.
[0004] (2) High energy density. Anodes such as lithium metal can be used to greatly increase energy density.
[0005] (3) Strong cycle performance. Solid electrolytes solve the problem of solid electrolyte interface film and lithium dendrite phenomenon formed by liquid electrolytes during the charge and discharge process, greatly improving the cycle performance and service life of lithium-ion batteries.
[0006] Based on the above advantages, sulfide all-solid-state batteries have become the development direction of the next generation of lithium-ion batteries. However, sulfide all-solid-state batteries still face many challenges, the most important of which is the assembly process. Unlike traditional liquid batteries that can use winding and lamination processes, all-solid-state batteries are limited by the use of solid electrolyte membranes and generally use lamination processes. Therefore, how to achieve continuous assembly and production of all-solid-state batteries under the lamination process is of great significance to the industrialization of all-solid-state batteries.
[0007] The current sulfide all-solid-state battery continuous assembly process has the following main defects:
[0008] (1) At present, sulfide all-solid-state batteries mostly adopt the lamination soft pack process, which requires the positive / negative electrodes and electrolyte membranes to be cut separately and then subjected to high-precision lamination. This method is inefficient and cannot meet the requirements of high-efficiency production processes;
[0009] (2) Some processes combine the positive and negative electrodes with the electrolyte and then cut them as a whole, and stack them in multiple layers. Although this method can improve production efficiency, it will cause the positive and negative electrodes and the electrolyte membrane to have uniform sizes during cutting, which will cause the positive and negative electrodes to contact after pressing and molding, eventually leading to short circuit failure of the battery cell;
[0010] (3) The existing molding technology only starts from the equipment and does not completely improve the internal film formation defects of solid-state batteries, such as electrolyte membrane transfer defects, resulting in low yield.
[0011] In summary, the existing sulfide all-solid-state battery continuous assembly process has the following problems: low assembly efficiency, easy short circuit of the battery after high-pressure molding, and low yield rate.
[0012] In view of this, the present invention is proposed. Summary of the invention
[0013] The object of the present invention is to provide a solid-state lithium-ion battery and a preparation method thereof, aiming to significantly improve the assembly yield rate and at the same time help improve assembly efficiency.
[0014] The present invention is achieved in that:
[0015] In a first aspect, the present invention provides a solid-state lithium-ion battery, comprising a positive electrode sheet, an electrolyte membrane and a negative electrode sheet, wherein the positive electrode sheet is bonded to the negative electrode sheet via the electrolyte membrane; an ionic liquid treatment layer is provided between the electrolyte membrane and the positive electrode sheet and / or the negative electrode sheet.
[0016] In an alternative embodiment of the present invention, the ionic liquid treatment layer is prepared by depositing the ionic liquid on the surface of the electrolyte membrane.
[0017] In an optional embodiment of the present invention, the solid-state lithium-ion battery further has at least one of features A to E:
[0018] A. Depositing the ionic liquid on the surface of the electrolyte membrane by vapor deposition to obtain an ionic liquid treatment layer;
[0019] B. The ionic liquid used in preparing the ionic liquid treatment layer is selected from at least one of 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium diamine, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate;
[0020] C. The thickness of the ionic liquid treatment layer is 5nm-1000nm;
[0021] D. The thickness of the electrolyte membrane is 10 μm-100 μm;
[0022] E. The electrolyte membrane includes a sulfide electrolyte and a binder, wherein the mass proportion of the sulfide electrolyte is 80%-99%; wherein the sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li3.875 Sn 0.875 As 0.125 At least one of S4 and Li4SnS4; the binder in the electrolyte membrane is selected from at least one of polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, polyvinyl alcohol, acrylates and nitrile-butadiene rubber.
[0023] In an optional embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer;
[0024] The negative electrode active layer includes 60%-85% of negative electrode active material, 1%-30% of conductive agent, 1%-30% of sulfide electrolyte and 0.1%-10% of binder by mass fraction;
[0025] The negative electrode sheet also has at least one of features F to J:
[0026] F, the negative electrode active material is selected from at least one of graphite, lithium titanate, silicon oxygen, silicon carbon and silicon-based alloy;
[0027] G, the conductive agent is selected from at least one of conductive carbon, acetylene black, vapor-grown carbon fiber and carbon nanotubes;
[0028] H. Sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125 At least one of S4 and Li4SnS4;
[0029] I. When the negative electrode is made by a dry process, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride binder, acrylic resin, polytetrafluoroethylene and styrene-butadiene rubber;
[0030] J. When the negative electrode plate is made by a wet process, the binder is selected from at least one of polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, polyvinyl alcohol, acrylic esters and nitrile-butadiene rubber.
[0031] In an optional embodiment of the present invention, the size of the positive electrode sheet is smaller than the size of the negative electrode sheet;
[0032] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer;
[0033] The positive electrode active layer comprises, by mass fraction, 60%-85% of positive electrode active material, 1%-30% of conductive agent, 1%-30% of sulfide electrolyte and 0.1%-10% of binder;
[0034] The positive electrode sheet also has at least one of the characteristics K to O:
[0035] K. The positive electrode active material is selected from at least one of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, nickel cobalt lithium manganese oxide, high nickel positive electrode material and lithium manganese rich positive electrode material.
[0036] L, a conductive agent is selected from at least one of carbon black, acetylene black, vapor-grown carbon fiber and carbon nanotubes;
[0037] M. Sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125S4 and at least one of Li4SnS4;
[0038] N. When the positive electrode is made by a dry process, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride binder, acrylic resin, polytetrafluoroethylene and styrene-butadiene rubber;
[0039] O. When the positive electrode sheet is made by a wet process, the binder is selected from at least one of polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, polyvinyl alcohol, acrylic esters and nitrile-butadiene rubber.
[0040] In a second aspect, the present invention further provides a method for preparing a solid-state lithium-ion battery in any of the above embodiments, comprising:
[0041] S1. Prepare a positive electrode material strip, a negative electrode material strip and an electrolyte material strip; the negative electrode material strip includes a negative electrode current collector and a negative electrode active layer attached to the negative electrode current collector, and the positive electrode material strip includes a positive electrode current collector and a positive electrode active layer attached to the positive electrode current collector; the electrolyte material strip includes a base film and an electrolyte film attached to the base film;
[0042] S2, transferring the electrolyte material strip onto the negative electrode active layer, so that the electrolyte membrane and the negative electrode active layer are bonded, and then tearing off the base film;
[0043] S3, laminating the positive electrode active layer on the positive electrode material strip with the electrolyte membrane laminated on the negative electrode active layer in step S2 to prepare a solid-state lithium-ion battery;
[0044] The preparation method further satisfies at least one of the following conditions:
[0045] Condition 1: In step S2, before transferring the electrolyte membrane onto the negative electrode active layer, an ionic liquid treatment layer is provided on the surface of the electrolyte membrane away from the base membrane;
[0046] Condition 2: In step S2, after the base film is torn off, an ionic liquid treatment layer is provided on the surface of the electrolyte membrane away from the negative electrode active layer.
[0047] In an optional embodiment of the present invention, the first negative electrode active layer and the second negative electrode active layer are respectively attached to both sides of the negative electrode current collector, and the first negative electrode active layer and the second negative electrode active layer are attached to the electrolyte membrane on the side away from the negative electrode current collector;
[0048] Wherein, in step S1, the positive electrode material strip, the negative electrode material strip and the electrolyte material strip are all in a continuous roll shape. After the negative electrode material strip and the electrolyte material strip are unwound, the electrolyte material strip is transferred to the negative electrode active layer by pressing. After the positive electrode material strip is unwound, the positive electrode active layer is pressed to the electrolyte membrane attached to the negative electrode active layer in step S2.
[0049] The pressing includes at least one of roller pressing, isostatic pressing and flat plate pressing.
[0050] In an optional embodiment of the present invention, the process of forming the electrolyte membrane includes: mixing a sulfide electrolyte, a binder and an electrolyte solvent according to the composition of the electrolyte membrane to obtain an electrolyte slurry, applying the electrolyte slurry on one side of the base membrane, and drying to form the electrolyte membrane;
[0051] The electrolyte solvent is selected from at least one of butyl butyrate, isobutyl isobutyrate, n-hexane, n-heptane, toluene, xylene, anisole, cyclohexanone and 1,3,5-trimethylbenzene; and / or
[0052] The material of the electrolyte base film is selected from at least one of polyethylene terephthalate, polyamide, polyimide, polypropylene, aluminum foil and stainless steel foil; and / or
[0053] The process of forming the ionic liquid treatment layer includes: depositing the ionic liquid on the electrolyte membrane by vapor deposition to form the ionic liquid treatment layer.
[0054] In an optional embodiment of the present invention, the negative electrode material strip is prepared by a dry process or a wet process;
[0055] When the negative electrode material strip is prepared by a dry process, the preparation process includes: mixing the raw materials in sequence at a low speed, shearing at a high speed and hot rolling according to the composition of the negative electrode active layer to obtain the negative electrode active layer, and laminating the negative electrode active layer to the negative electrode current collector;
[0056] When the negative electrode material strip is prepared by a wet process, the preparation process includes: mixing various raw materials according to the composition of the negative electrode active layer to form a homogenous slurry, coating it on the negative electrode current collector, and drying it.
[0057] In an optional embodiment of the present invention, the positive electrode material strip is cut so that the size of the positive electrode material strip is smaller than that of the negative electrode material strip, the positive electrode active layer on the positive electrode material strip is laminated with the electrolyte membrane laminated on the negative electrode active layer in step S2, and then cut and stacked to obtain a solid-state lithium-ion battery;
[0058] The positive electrode strip is prepared by a dry process or a wet process;
[0059] When the positive electrode material strip is prepared by a dry process, the preparation process includes: mixing the raw materials at a low speed, shearing at a high speed and hot rolling in sequence according to the composition of the positive electrode active layer to obtain the positive electrode active layer, and laminating the positive electrode active layer to the positive electrode current collector;
[0060] When the positive electrode material strip is prepared by a wet process, the preparation process includes: mixing various raw materials according to the composition of the positive electrode active layer to form a homogenous slurry, coating it on the positive electrode current collector, and drying it.
[0061] The present invention has the following beneficial effects: by laminating the positive electrode sheet with the negative electrode sheet through the electrolyte membrane, an ionic liquid treatment layer is introduced between the electrolyte membrane and the positive electrode sheet, or an ionic liquid treatment layer is introduced between the electrolyte membrane and the negative electrode sheet, or an ionic liquid treatment layer is introduced between the electrolyte membrane and both the positive electrode sheet and the negative electrode sheet, so that the electrolyte membrane is easy to be successfully transferred and the assembly yield can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0063] Figure 1 A schematic diagram of the structure of an electrolyte membrane provided by an embodiment of the present invention;
[0064] Figure 2 A schematic diagram of preparing a composite negative electrode material strip provided in an embodiment of the present invention;
[0065] Figure 3 A composite negative electrode winding process is provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0066] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0067] An embodiment of the present invention provides a method for preparing a solid-state lithium-ion battery, comprising the following steps:
[0068] S1. Preparation of positive electrode material strip, negative electrode material strip and electrolyte material strip
[0069] Prepare the positive electrode material strip, negative electrode material strip and electrolyte material strip respectively and set them aside. The preparation process of the three material strips is described below:
[0070] (1) Preparation of positive electrode strip
[0071] The positive electrode material strip includes a positive electrode current collector and a positive electrode active layer attached to the positive electrode current collector. The positive electrode material strip is obtained by forming the positive electrode active layer on the positive electrode current collector. The positive electrode material strip can be prepared by a dry process or a wet process, and the specific preparation process is not limited.
[0072] In some embodiments, the positive electrode current collector may be aluminum foil, but is not limited thereto.
[0073] In some embodiments, the positive electrode active layer includes 60%-85% positive electrode active material, 1%-30% conductive agent, 1%-30% sulfide electrolyte and 0.1%-10% binder by mass. The amount of each component is preferably controlled within the above range to further improve the electrochemical performance of the battery.
[0074] Specifically, the mass fraction of the positive electrode active material can be 60%, 65%, 70%, 75%, 80%, 85%, etc., the mass fraction of the conductive agent can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., the mass fraction of the sulfide electrolyte can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., and the mass fraction of the binder can be 0.1%, 0.5%, 1.0%, 3.0%, 5.0%, 8.0%, 10.0%, etc.
[0075] The positive electrode active material is selected from lithium manganese oxide (LiMn2O4), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), lithium nickel cobalt manganese oxide (LiNi x Co y Mn z O2), high nickel positive electrode materials (LiNi x Co y Al z O2) and at least one of the lithium-rich manganese positive electrode materials, which can be at least one or more of the above commonly used positive electrode active materials, LiNi x Co y Mn z O2 and LiNi x Co y Alz The parameter values in the chemical formula of O2 satisfy: x+y+z=1, 0 <x<1,0<y<1,0<z<1。
[0076] The conductive agent is selected from at least one of carbon black, acetylene black, vapor grown carbon fiber (VGCF) and carbon nanotube (CNT), and can be any one or more of the above. The sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125S4 and at least one of Li4SnS4, and can be any one or more of the above.
[0077] When the positive electrode material strip is prepared by a dry process, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride binder, acrylic resin, polytetrafluoroethylene and styrene-butadiene rubber, and may be any one or more of the above. When the positive electrode material strip is prepared by a wet process, the binder is selected from at least one of polyvinylidene fluoride binder (which may be a PVDF modified polymer), silicone rubber (SR), styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), acrylic ester (CMA) and nitrile-butadiene rubber (NBR), and may be any one or more of the above.
[0078] When the positive electrode material strip is prepared by a dry process, the preparation process includes: mixing the raw materials at a low speed, shearing at a high speed and hot rolling in sequence according to the composition of the positive electrode active layer to obtain the positive electrode active layer, and laminating the positive electrode active layer to the positive electrode current collector to obtain the positive electrode material strip. The speed can be controlled to be 50-200r / min during low-speed mixing, 800-1500r / min during high-speed shearing, and the rolling temperature can be controlled to be 60℃-220℃ during hot rolling.
[0079] When the positive electrode material strip is prepared by a wet process, the preparation process includes: mixing and homogenizing various raw materials according to the composition of the positive electrode active layer, coating the slurry on the positive electrode collector, and obtaining the positive electrode material strip after drying.
[0080] In some embodiments, whether it is a dry process or a wet process, the thickness of the positive electrode active layer can be controlled to be 50 μm-400 μm to ensure the electrochemical performance of the battery.
[0081] It should be noted that the "positive electrode strip" refers to the material before rolling, and the positive electrode strip is the positive electrode sheet in the final product.
[0082] (2) Preparation of negative electrode strip
[0083] The negative electrode material strip includes a negative electrode current collector and a negative electrode active layer. The negative electrode material strip is obtained by forming a negative electrode active layer on the negative electrode current collector. The negative electrode material strip can be prepared by a dry process or a wet process, and the specific preparation process is not limited.
[0084] In some embodiments, the negative electrode current collector may be copper foil, but is not limited thereto.
[0085] In some embodiments, the negative electrode active layer includes 60%-85% of negative electrode active material, 1%-30% of conductive agent, 1%-30% of sulfide electrolyte and 0.1%-10% of binder by mass. The amount of each component is preferably controlled within the above range to further improve the electrochemical performance of the battery.
[0086] Specifically, the mass fraction of the negative electrode active material can be 60%, 65%, 70%, 75%, 80%, 85%, etc., the mass fraction of the conductive agent can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., the mass fraction of the sulfide electrolyte can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., and the mass fraction of the binder can be 0.1%, 0.5%, 1.0%, 3.0%, 5.0%, 8.0%, 10.0%, etc.
[0087] Furthermore, the negative electrode active material is selected from at least one of graphite, lithium titanate, silicon oxygen, silicon carbon and silicon-based alloy, and can be any one or more of the above. The conductive agent is selected from at least one of conductive carbon, acetylene black, vapor-grown carbon fiber (VGCF) and carbon nanotube (CNT), and can be any one or more of the above. The sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125 At least one of S4 and Li4SnS4 can be any one or more of the above.
[0088] Furthermore, the type of binder in the negative electrode active layer is slightly different according to the preparation process. When the negative electrode material strip is prepared by a dry process, the binder is selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride binder (which can be a modified copolymer of PVDF), acrylic resin (PAA), polytetrafluoroethylene (PTFE) and styrene-butadiene rubber (SBR), and can be at least one or more of the above. When the negative electrode material strip is prepared by a wet process, the binder is selected from at least one of polyvinylidene fluoride binder (which can be a modified copolymer of PVDF), silicone rubber (SR), styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), acrylic esters (CMA) and nitrile-butadiene rubber (NBR), and can be any one or more of the above.
[0089] When the negative electrode material strip is prepared by dry process, the preparation process includes: according to the composition of the negative electrode active layer, the raw materials are sequentially subjected to low-speed mixing, high-speed shearing and hot rolling to obtain the negative electrode active layer, and the negative electrode active layer is bonded to the negative electrode current collector to obtain the negative electrode material strip. Among them, the speed can be controlled to be 50-200r / min during low-speed mixing; the speed can be controlled to be 800-1500r / min during high-speed shearing; and the rolling temperature can be controlled to be 60℃-220℃ during hot rolling.
[0090] When the negative electrode material strip is prepared by a wet process, the preparation process includes: mixing various raw materials according to the composition of the negative electrode active layer to form a homogenous slurry, coating it on the negative electrode current collector, and obtaining the negative electrode material strip after drying.
[0091] In some embodiments, whether it is a dry process or a wet process, the thickness of the negative electrode active layer can be controlled to be 40 μm-400 μm to ensure the electrochemical performance of the battery.
[0092] (3) Preparation of electrolyte strip
[0093] The electrolyte material strip includes a base film and an electrolyte membrane attached to the base film. In actual operation, the preparation process of the electrolyte membrane includes: mixing the components according to the composition of the electrolyte membrane to obtain an electrolyte slurry, coating the electrolyte slurry on one side of the base film, and forming an electrolyte membrane after drying.
[0094] In some embodiments, the raw materials for preparing the electrolyte membrane include sulfide electrolyte, binder and electrolyte solvent. The electrolyte solvent evaporates after drying, so the electrolyte membrane in the product contains sulfide electrolyte and binder. In the electrolyte membrane, the mass proportion of sulfide electrolyte is 80%-99% (such as 80%, 85%, 90%, 95%, 99%, etc.), and the rest can be binder. The electrolyte material strip can be prepared by the following process. According to the composition of the electrolyte membrane, the sulfide electrolyte, binder and electrolyte solvent are mixed to obtain electrolyte slurry, and the electrolyte slurry is applied to one side of the electrolyte base membrane, and the electrolyte membrane roll is obtained after drying.
[0095] Among them, the sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125 At least one of S4 and Li4SnS4 can be any one or more of the above, but not limited to the above. The binder in the electrolyte membrane is selected from at least one of polyvinylidene fluoride binders (which can be PVDF modified polymers), SR, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), CMA and nitrile-butadiene rubber (NBR), and can be any one or more of the above, but not limited to the above. The electrolyte solvent is selected from at least one of butyl butyrate, isobutyl isobutyrate, n-hexane, n-heptane, toluene, xylene, anisole, cyclohexanone and 1,3,5-trimethylbenzene, and can be any one or more of the above, but not limited to the above.
[0096] The electrolyte base membrane is a substrate, and its material is selected from at least one of polyethylene terephthalate (PET), polyamide (PA), polyimide (PI), polypropylene (PP), aluminum foil and stainless steel foil. It can be any one or more of the above, but not limited to the above.
[0097] In some embodiments, please refer to Figure 1 The preparation process of the electrolyte strip is to sequentially form an electrolyte membrane and an ionic liquid treatment layer on the electrolyte base membrane. By introducing the ionic liquid treatment layer, the surface adhesion and density of the electrolyte membrane can be improved, and the treated electrolyte membrane roll is obtained for use. That is to say, before the electrolyte membrane is transferred to the negative electrode active layer, the ionic liquid treatment layer is set on the surface of the electrolyte membrane away from the base membrane.
[0098] The ionic liquid treatment layer can be prepared by vapor deposition, but is not limited thereto. By combining the vapor deposition process, the ionic liquid can be well combined with the sulfur bonds between the sulfide electrolyte membrane, and the ionic bond chemical action can enhance the interaction between the ionic liquid and the sulfide electrolyte, thereby improving the density of the electrolyte membrane surface and the mechanical strength of the electrolyte membrane. In addition, the ionic liquid itself has a certain viscosity, which can be beneficial to the success rate of the transfer composite between the electrolyte membrane and the negative electrode in the later stage.
[0099] It should be added that, combined with the vapor deposition process, the fluidity of the ionic liquid itself can fill the micropores in the electrolyte membrane to increase the density of the membrane and improve the ionic conductivity. The self-leveling of the ionic liquid can improve the flatness of the electrolyte membrane surface, thereby improving the solid-solid contact effect between the electrolyte membrane and the electrode sheet, reducing the impedance between the electrolyte membrane and the electrode sheet, and improving battery performance. In short, ionic liquids can effectively improve the strength and ionic conductivity of the membrane by filling micropores and the ionic bonding between self-leveling and electrolytes, and greatly improve the efficiency of subsequent transfer.
[0100] Further, the ionic liquid contained in the ionic liquid treatment layer is selected from at least one of 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium diamine, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, and can be any one or more of the above, but not limited to the above.
[0101] In some embodiments, the thickness of the electrolyte base film is 10 μm-100 μm (such as 10 μm, 30 μm, 50 μm, 80 μm, 100 μm, etc.), the thickness of the electrolyte membrane is 15 μm-120 μm, and the deposition thickness of the ionic liquid treatment layer is 5 nm-1000 nm (such as 5 μm, 10 μm, 50 μm, 100 μm, 300 μm, 500 μm, 800 μm, 1000 μm, etc.). By optimizing the thickness of each layer, especially the deposition thickness of the ionic liquid treatment layer, the high ionic conductivity of the electrolyte surface can be effectively retained, which has a certain effect on improving battery performance.
[0102] In other embodiments, when preparing the electrolyte membrane, the ionic liquid treatment layer may not be introduced, but the ionic liquid treatment layer is introduced in step S2, as described in detail in step S2.
[0103] In some embodiments, the positive electrode material strip, the negative electrode material strip, and the electrolyte material strip may be in a continuous roll form so as to be bonded together by pressing.
[0104] S2. Bonding the electrolyte membrane to the negative electrode active layer
[0105] The electrolyte tape is transferred onto the negative electrode active layer to make the electrolyte membrane adhere to the negative electrode active layer, and then the base film is torn off. At this time, the base film is located on the side of the electrolyte membrane away from the negative electrode active layer.
[0106] In some embodiments, the first negative electrode active layer and the second negative electrode active layer are respectively attached to both sides of the negative electrode current collector, and the first negative electrode active layer and the second negative electrode active layer are attached to the electrolyte membrane on the side away from the negative electrode current collector. Figure 2 As shown, the electrolyte membranes prepared in S1 are respectively compounded on the front and back sides of the negative electrode material strip, which are respectively called the first electrolyte membrane and the second electrolyte membrane. The two wet-process electrolyte membranes are respectively bonded and transferred to the front and back sides of the negative electrode material strip.
[0107] In actual operation, the first electrolyte membrane and the second electrolyte membrane can be transferred to the front and back sides of the negative electrode material strip by multi-roller bonding. During the multi-roller bonding, the multi-roller composite line pressure is controlled to be 10MPa-500MPa, and the roller temperature is 25℃-200℃. After the transfer is completed, the tape is rolled up to obtain a composite negative electrode material strip.
[0108] Specifically, the roller composite line pressure can be 10 MPa, 50 MPa, 100 MPa, 200 MPa, 300 MPa, 400 MPa, 500 MPa, etc., and the roller temperature can be 25°C, 50°C, 100°C, 150°C, 200°C, etc.
[0109] According to the different timings of introducing the ionic liquid treatment layer, there are two cases as follows: (1) the ionic liquid treatment layer has been introduced in S1, that is, before the electrolyte membrane is transferred to the negative electrode active layer, the ionic liquid treatment layer is deposited on the surface of the electrolyte membrane away from the base membrane, and after step S2, the ionic liquid treatment layer is provided between the negative electrode active layer and the electrolyte membrane. (2) After the base membrane is torn off in step S2, the ionic liquid treatment layer is deposited on the surface of the electrolyte membrane away from the negative electrode active layer, and at this time, the ionic liquid treatment layer is provided between the positive electrode active layer and the electrolyte membrane.
[0110] In some embodiments, the negative electrode material strip and the electrolyte material strip are both in a continuous roll form. After the negative electrode material strip and the electrolyte material strip are unwound, the electrolyte material strip is transferred to the negative electrode active layer by pressing. The pressing method is not limited, and it can be at least one of roll pressing, isostatic pressing and flat plate pressing, preferably flat plate pressing. Pressing can also include hot pressing and cold pressing, multiple pressings can be set, and multiple pressing methods can be mixed, such as cold rolling first, then flat plate hot pressing, or flat plate hot pressing first, then flat plate cold pressing.
[0111] The specific operation can be as follows Figure 3As shown, the electrolyte layer is bonded on both sides of the negative electrode material strip (also called the negative electrode coil), and the two are conveyed and subjected to hot pressing, cold pressing, and then conveyed to obtain a composite negative electrode coil, and the electrolyte layer base is rolled up. By introducing the flat-plate hot pressing and cold pressing processes, the transfer composite yield rate can be effectively improved, and the efficiency of transfer composite can be improved by combining with the conveyor belt. A double steel belt press can be used for the pressing operation. The parameters of the double steel belt press are 10Mpa-500Mpa, roller temperature: 25-200°, and transmission efficiency: 1-30m / min. After the transfer is completed, the electrolyte membrane base is rolled up, that is, the electrolyte membrane transfer is completed to obtain a composite negative electrode coil. The double steel belt press is used, combined with the roller pressing method and the flat plate pressing method of the traditional composite transfer, to improve the success rate and yield rate of the composite transfer;
[0112] S3. Laminating the positive electrode strip
[0113] The positive electrode active layer on the positive electrode material strip is laminated with the electrolyte membrane laminated on the negative electrode active layer in step S2 to obtain a solid-state lithium-ion battery. The structure of the obtained battery is in the following order: positive electrode current collector, positive electrode active layer, electrolyte membrane, negative electrode active layer, negative electrode current collector. The structure also includes an ionic liquid treatment layer. The position of the ionic liquid treatment layer has three situations: (1) between the positive electrode active layer and the electrolyte membrane; (2) between the electrolyte membrane and the negative electrode active layer; (3) an ionic liquid treatment layer is provided between the positive electrode active layer and the electrolyte membrane and between the electrolyte membrane and the negative electrode active layer.
[0114] S4, positive electrode strip cutting
[0115] The positive electrode material strip is cut so that the size of the positive electrode material strip is smaller than that of the negative electrode material strip. Specifically, the size of the positive electrode material strip is smaller than that of the negative electrode material strip, which means that the size of the positive electrode material strip is smaller than that of the negative electrode material strip in terms of both length and width. This can avoid the final cell cutting causing the positive and negative electrodes to be the same size, resulting in short circuit failure of the cell.
[0116] In some embodiments, the positive electrode strip may be laser cut to obtain positive electrode sheets of a specific size, and the cutting depth may be controlled by the laser power.
[0117] In some embodiments, the positive electrode active layer on the positive electrode material strip is laminated to the electrolyte membrane laminated to the negative electrode active layer in step S2, and then cut and stacked to obtain a solid-state lithium-ion battery. The cutting process is not limited, and laser cutting can be used; the stacking process is not limited, and suction cup stacking can be used for stacking, and the stacking accuracy is less than 0.1 mm.
[0118] It should be noted that the preparation method of the solid-state lithium-ion battery provided in the embodiment of the present invention adopts a double-layer transfer electrolyte layer process on the positive / back side of the negative electrode material strip, and relies on the negative electrode sheet to realize the winding and unwinding process of the electrolyte layer, thereby transforming the traditional all-solid-state battery assembly that can only stack single layers into a roll-to-roll docking process. The entire process adopts a roll-to-roll process, which can greatly improve the production efficiency of sulfide all-solid-state batteries.
[0119] The embodiment of the present invention provides a solid-state lithium-ion battery, which can be prepared by the above-mentioned preparation method, including a positive electrode sheet, an electrolyte membrane and a negative electrode sheet, wherein the positive electrode sheet is bonded to the negative electrode sheet through the electrolyte membrane; an ionic liquid treatment layer is provided between the electrolyte membrane and the positive electrode sheet and / or the negative electrode sheet. The ionic liquid treatment layer can be located between the electrolyte membrane and the positive electrode sheet, or between the electrolyte membrane and the negative electrode sheet, or both between the electrolyte membrane and the positive electrode sheet and between the electrolyte membrane and the negative electrode sheet.
[0120] In some embodiments, the size of the positive electrode strip is smaller than that of the negative electrode strip, so as to avoid the failure of the battery cell due to the same size of the positive and negative electrodes and short circuit, thereby improving the success rate of assembly.
[0121] It should be noted that the thickness and composition of the positive electrode material strip / electrolyte membrane / negative electrode material strip / electrolyte membrane in the solid-state lithium-ion battery refer to the introduction of the preparation method and will not be repeated here.
[0122] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0123] Example 1
[0124] This embodiment provides a method for preparing a solid-state lithium-ion battery, comprising the following steps:
[0125] (1) Silica material (SiO / C-450, the same below), Li3PS4, VGCF (purchased from Kejing, the same below) and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 70:25:3:2, mixed at a low speed (100 r / min) for 0.1 h, and sheared at a high speed (1000 r / min) for 0.3 h, and then hot rolled at 100°C to form a negative electrode active layer with a thickness of 220 μm. The negative electrode active layer was compounded with a 7 μm double-sided carbon-coated copper foil and die-cut to prepare a negative electrode coil.
[0126] (2) xylene, n-heptane and PVDF are mixed to prepare a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to prepare a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98 and the solid content is 45% to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a 11 μm PET substrate, and after drying at 80° C., an electrolyte membrane with a thickness of 40 μm is formed, and the electrolyte sheet is obtained after die cutting.
[0127] (3) 1-ethyl-3-methylimidazolium ethyl sulfate is prepared into an ionic liquid, and the electrolyte sheet obtained in step (2) is placed in a vapor deposition assembly, and the surface of the electrolyte membrane is deposited with the ionic liquid to a deposition thickness of 50 nm to obtain an electrolyte strip. The process parameters of the deposition process are as follows: the existing conventional vapor deposition method can be used.
[0128] (4) The electrolyte material strip obtained in step (3) and the negative electrode material strip in step (1) are pressed and transferred by double steel belts to prepare a composite negative electrode material strip, and the base film is peeled off. The double steel belt pressing method (10m / min, 100°) is used.
[0129] (5) NCM811@Li2TiO3 (i.e., NCM811 positive electrode particles coated with 3 nm thick Li2TiO3, homemade) was used as the positive electrode active material, Li6PS5Cl was used as the positive electrode electrolyte, CNT was used as the conductive agent, and modified polytetrafluoroethylene (PTFE functional group substituted, purchased from DuPont TE3885, the same below) was used as the positive electrode binder. The mixture was mixed in a mass ratio of 75:22:2:1, mixed at a low speed (100 r / min) for 0.1 h, and sheared at a high speed (1000 r / min) for 0.15 h, and then hot rolled at 110°C to form a 220 μm positive electrode active layer. The positive electrode active layer was compounded with 11 μm carbon-coated aluminum foil to form a positive electrode tape, which was die-cut to prepare a positive electrode tape.
[0130] (6) The composite negative electrode roll of step (4) and the positive electrode material of step (5) are laser cut to obtain electrode sheets of a specific size battery cell (170×190 mm), and the positive electrode sheets and the negative electrode sheets with electrolyte layers are laminated to form a sulfide all-solid-state battery.
[0131] Example 2 (Comparison of forming an ionic liquid layer on the negative electrode surface)
[0132] This embodiment provides a method for preparing a solid-state lithium-ion battery, comprising the following steps:
[0133] (1) Silica material (SiO / C-450, the same below), Li3PS4, VGCF (purchased from Kejing, the same below) and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 70:25:3:2, mixed at a low speed (100 r / min) for 0.1 h, and sheared at a high speed (1000 r / min) for 0.3 h, and then hot rolled at 100°C to form a negative electrode active layer with a thickness of 220 μm. The negative electrode active layer was compounded with a 7 μm double-sided carbon-coated copper foil and die-cut to prepare a negative electrode coil.
[0134] (2) xylene, n-heptane and PVDF are mixed to prepare a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to prepare a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98 and the solid content is 45% to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a 11 μm PET substrate, and after drying at 80° C., an electrolyte membrane with a thickness of 40 μm is formed, and the electrolyte sheet is obtained after die cutting.
[0135] (3) 1-ethyl-3-methylimidazolium ethyl sulfate is prepared into an ionic liquid, and the composite negative electrode obtained in step (1) is placed in a vapor deposition assembly, and the surface of the composite negative electrode is deposited with the ionic liquid to a deposition thickness of 50 nm to obtain a composite negative electrode strip. The process parameters of the deposition process are as follows: the existing conventional vapor deposition method can be used.
[0136] (4) The electrolyte material strip obtained in step (2) and the negative electrode material strip in step (3) are pressed and transferred by double steel belts to prepare a composite negative electrode material strip, and the base film is torn off. The double steel belt pressing method (10m / min, 100°) is used.
[0137] (5) Take NCM811@Li2TiO3 (i.e., NCM811 positive electrode particles coated with 3 nm thick Li2TiO3, homemade) as the positive electrode active material, Li6PS5Cl as the positive electrode electrolyte, CNT as the conductive agent, and modified polytetrafluoroethylene (PTFE functional group replacement, purchased from DuPont TE3885) as the positive electrode binder, and mix them in a mass ratio of 75:22:2:1, mix at a low speed (100 r / min) for 0.1 h, and high speed shear (1000 r / min) for 0.15 h, and then hot roll press at 110°C to a 220 μm positive electrode active layer. The positive electrode active layer is compounded with 11 μm carbon-coated aluminum foil to form a positive electrode tape, and the positive electrode tape is prepared by die cutting.
[0138] (6) The composite negative electrode roll of step (4) and the positive electrode material of step (5) are laser cut to obtain electrode sheets of a specific size battery cell (170×190 mm), and the positive electrode sheets and the negative electrode sheets with electrolyte layers are laminated to form a sulfide all-solid-state battery.
[0139] Comparative Example 1
[0140] This comparative example provides a method for preparing a solid-state lithium-ion battery, comprising the following steps:
[0141] (1) Silicon oxide material, Li3PS4, VGCF and PVDF were mixed in a mass ratio of 70:25:3:2, PVDF was dissolved in toluene to obtain a mixed glue solution, the mixed glue solution was mixed with other components to obtain a negative electrode slurry, and the negative electrode slurry was coated on a 7 μm double-sided carbon-coated copper foil, and the coating surface density was controlled to be 10 mg / cm 2 After drying at 60°C, the negative electrode material strip is prepared for use.
[0142] (2) xylene, n-heptane and PVDF are mixed to prepare a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to prepare a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98, to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a 11 μm PET substrate, and dried at 80° C. to form an electrolyte membrane with a thickness of 50 μm on the surface of the substrate for later use.
[0143] (3) The negative electrode material strips and the electrolyte membrane strips of step (1) and step (2) are prepared by roller pressing (speed: 5 m / min, 100°) to obtain a composite negative electrode material strip for use.
[0144] (4) Take NCM811@Li2TiO3 (NCM811 positive electrode particles with a surface coating of 3 nm thick Li2TiO3 as the positive electrode active material, Li6PS5Cl as the positive electrode electrolyte, CNT as the conductive agent, and PTFE as the positive electrode binder, and mix them in a mass ratio of 75:22:2:1. After low-speed (100 r / min) mixing for 0.1 h, high-speed shearing (1000 r / min) for 0.12 h, and then hot rolling at 110°C to form a 220 um dry positive electrode film. The dry positive electrode film is compounded with 11 μm carbon-coated aluminum foil to form a positive electrode material strip for use.
[0145] (5) Cutting the positive electrode material strip obtained in step (4) by controlling the laser power to obtain a cut positive electrode material strip.
[0146] (6) Compounding the composite negative electrode material strip obtained in step (3) and the positive electrode material strip obtained in step (5) with multiple rows of rollers to form a composite single-layer battery cell structure, which is then cut and stacked to finally form a sulfide all-solid-state battery.
[0147] Comparative Example 2
[0148] This comparative example provides a method for preparing a solid-state lithium-ion battery, comprising the following steps:
[0149] (1) Silica material, Li3PS4, VGCF and polytetrafluoroethylene (PTFE) were mixed at a mass ratio of 70:25:3:2 at a low speed (100 r / min) for 0.2 h, and sheared at a high speed (1000 r / min) for 0.25 h. The mixture was then hot rolled at 100°C to form a 220 μm dry-process negative electrode film. The dry-process negative electrode film was then composited with a 7 μm double-sided carbon-coated copper foil to prepare a negative electrode tape for use.
[0150] (2) xylene, n-heptane and PVDF are mixed to prepare a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to prepare a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98, to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a 11 μm PET substrate, and dried at 80° C. to form an electrolyte membrane with a thickness of 50 μm on the surface of the substrate for later use.
[0151] (3) The negative electrode material strips and the electrolyte membrane strips of step (1) and step (2) are prepared by roller pressing (speed: 5 m / min, 100°) to obtain a composite negative electrode material strip for use.
[0152] (4) Take NCM811@Li2TiO3 (NCM811 positive electrode particles with a surface coating of 3 nm thick Li2TiO3 as the positive electrode active material, Li6PS5Cl as the positive electrode electrolyte, CNT as the conductive agent, and modified PTFE as the positive electrode binder, and mix them in a mass ratio of 75:22:2:1, mix them at a low speed (100 r / min) for 0.1 h, and high-speed shear (1000 r / min) for 0.12 h, and then hot roll press them at 110°C to a 220 um dry positive electrode film. The dry positive electrode film is compounded with 11 μm carbon-coated aluminum foil to form a positive electrode material strip for use.
[0153] (5) Cutting the positive electrode material strip obtained in step (4) by controlling the laser power to obtain a cut positive electrode material strip.
[0154] (6) Compounding the composite negative electrode material strip of step (3) and the positive electrode material strip of step (5) by multiple rows of rollers to form a composite single-layer battery cell structure, and then cutting and stacking to finally form a sulfide all-solid-state battery.
[0155] Comparative Example 3
[0156] This comparative example provides a method for preparing a solid-state lithium-ion battery, comprising the following steps:
[0157] (1) Silica material, Li3PS4, VGCF and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 70:25:3:2, mixed at a low speed (100 r / min) for 0.2 h, and sheared at a high speed (1000 r / min) for 0.22 h, and then hot rolled at 110°C to a dry-process negative electrode film with a thickness of 220 μm. The dry-process negative electrode film was composited with a 7 μm double-sided carbon-coated copper foil to prepare a negative electrode material strip for use.
[0158] (2) xylene, n-heptane and PVDF are mixed to prepare a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to prepare a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98, to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a 11 μm PET substrate, and dried at 80° C. to form an electrolyte membrane with a thickness of 50 μm on the surface of the substrate for later use.
[0159] (3) The negative electrode material strips and the electrolyte membrane strips of step (1) and step (2) are prepared by roller pressing (speed: 5 m / min, 100°) to obtain a composite negative electrode material strip for use.
[0160] (4) Take NCM811@Li2TiO3 (the surface of NCM811 positive electrode particles is coated with 3 nm thick Li2TiO3 as the positive electrode active material, Li6PS5Cl as the positive electrode electrolyte, CNT as the conductive agent, and modified PVDF as the positive electrode binder, and use them according to the mass ratio of 75:22:2:1. Use butyl butyrate to dissolve the modified PVDF to obtain a mixed glue. After stirring and mixing the mixed glue with other components to obtain a positive electrode slurry, the positive electrode slurry is coated on a 11 μm double-sided carbon-coated aluminum foil, and the coating surface density is controlled to be 22 mg / cm 2 After 110℃ hot roller composite pressing, the positive electrode material strip is obtained for use.
[0161] (5) Cutting the positive electrode material strip obtained in step (4) by controlling the laser power to obtain a cut positive electrode material strip.
[0162] (6) Compounding the composite negative electrode material strip of step (3) and the positive electrode material strip of step (5) by multiple rows of rollers to form a composite single-layer battery cell structure, and then cutting and stacking to finally form a sulfide all-solid-state battery.
[0163] Comparative Example 4
[0164] Compared with Comparative Example 1, the only difference is that step (4) is removed, the composite negative electrode material strip and the positive electrode material strip are directly composited, and finally laser cutting and lamination are used to prepare a sulfide all-solid-state battery.
[0165] Comparative Example 5
[0166] The only difference from Example 1 is that step (3) is not performed and step (4) is performed directly, that is, no ionic liquid treatment layer is formed.
[0167] Test Example 1
[0168] The electrochemical properties of the solid-state lithium-ion batteries prepared in the examples and comparative examples were tested, and the results are shown in Table 1.
[0169] Test conditions: Xinwei 5V6A charger and discharger, 25℃, 0.05C charging and discharging.
[0170] Yield test method: micro short circuit tester
[0171] Table 1 Electrochemical performance test results of examples and comparative examples
[0172]
[0173] It can be seen that the yield rate of the comparative example is significantly lower. The preparation method provided in the embodiment of the present invention can significantly improve the yield rate and molding efficiency of the battery, and is suitable for industrial applications.
[0174] In order to prove that the present invention can improve the composite negative electrode transfer yield and composite negative electrode forming efficiency by introducing an ionic liquid treatment layer, the following examples and comparative examples are also provided:
[0175] Case 1
[0176] (1) Weigh silicon oxide material, Li3PS4, VGCF and PVDF in a mass ratio of 70:25:3:2, use toluene to dissolve PVDF to obtain a mixed glue solution, stir the mixed glue solution with other components to obtain a negative electrode slurry, and apply the negative electrode slurry on a double-sided carbon-coated copper foil to prepare a negative electrode coil for use.
[0177] (2) xylene, n-heptane and PVDF are mixed to prepare a gel (to obtain a solution with a solid content of 80%) to obtain a mixed gel solution; the mixed gel solution and Li6PS5Cl are mixed by ball milling in proportion to prepare a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98, to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a PET substrate, and dried to form an electrolyte diaphragm tape on the surface of the substrate for later use.
[0178] (3) The negative electrode coil of step (1) and the electrolyte separator tape are rolled into a composite negative electrode coil by roll forming (speed: 5 m / min, 100°) for use.
[0179] Case 2
[0180] (1) Weigh silicon oxide material, Li3PS4, VGCF and PVDF in a mass ratio of 70:25:3:2, use toluene to dissolve PVDF to obtain a mixed glue solution, stir the mixed glue solution with other components to obtain a negative electrode slurry, and apply the negative electrode slurry on a double-sided carbon-coated copper foil to prepare a negative electrode coil for use.
[0181] (2) xylene, n-heptane and PVDF are mixed to obtain a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to obtain a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98, to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a PET substrate, and dried to form an electrolyte diaphragm tape on the surface of the substrate for later use.
[0182] (3) The negative electrode coil of step (1) and the electrolyte separator tape are pressed by flat plate pressing (100°, 1 min) to obtain a composite negative electrode coil for use.
[0183] Case 3
[0184] (1) Weigh silicon oxide material, Li3PS4, VGCF and PVDF in a mass ratio of 70:25:3:2, use toluene to dissolve PVDF to obtain a mixed glue solution, stir the mixed glue solution with other components to obtain a negative electrode slurry, and apply the negative electrode slurry on a double-sided carbon-coated copper foil to prepare a negative electrode coil for use.
[0185] (2) xylene, n-heptane and PVDF are mixed to obtain a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to obtain a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98, to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a PET substrate, and dried to form an electrolyte diaphragm tape on the surface of the substrate for later use.
[0186] (3) The negative electrode coils and the electrolyte membrane tape of step 1 and step 2 are pressed by double steel belts (10 m / min, 100°) to obtain a composite negative electrode coil for use.
[0187] Case 4
[0188] (1) Silica material, Li3PS4, VGCF and polytetrafluoroethylene (PTFE) were weighed in a mass ratio of 70:25:3:2, mixed at a low speed (100 r / min), sheared at a high speed (1000 r / min) and hot rolled to a 220 um dry-process negative electrode film, and the dry-process negative electrode film was compounded with a double-sided carbon-coated copper foil and die-cut to prepare a negative electrode sheet.
[0189] (2) xylene, n-heptane and PVDF are mixed to prepare a mixed glue solution; the mixed glue solution and Li6PS5Cl are mixed by ball milling in proportion to prepare a slurry, wherein the mass ratio of PVDF to Li6PS5Cl is 2:98, to obtain an electrolyte slurry; the electrolyte slurry is coated on the surface of a PET substrate, and die-cut to prepare an electrolyte sheet.
[0190] (3) 1-ethyl-3-methylimidazolium ethyl sulfate is prepared into an ionic liquid, and the electrolyte sheet of step (2) is placed in a vapor deposition assembly, and the surface of the electrolyte membrane is deposited with the ionic liquid, with a deposition thickness of 50 nm, to obtain a treated electrolyte layer.
[0191] (4) The negative electrode coils of step (1) and step (3) and the treated electrolyte membrane tape are pressed by double steel belts (10 m / min, 100°) to obtain a composite negative electrode coil for use.
[0192] The transfer yield rate and forming efficiency of the composite negative electrode of test cases 1-4 are shown in Table 2.
[0193] Test methods: (1) Test method for composite negative electrode transfer yield: battery cell micro short circuit tester. (2) Test method for composite negative electrode forming efficiency: reel weight per unit time.
[0194] Table 2 Case 1-4 Composite negative electrode transfer yield and composite negative electrode forming rate
[0195]
[0196] It can be seen that in case 4, by introducing the ionic liquid treatment layer, the transfer yield of the composite negative electrode can be significantly improved, which is also conducive to improving the composite negative electrode forming efficiency. This may be because: the surface treatment of the electrolyte layer with ionic liquids can improve the adhesion of the electrolyte layer and reduce the interface impedance, thereby improving the transfer success rate and yield rate.
[0197] In summary, the present invention provides a solid-state lithium-ion battery and a preparation method thereof, which have the following advantages over the traditional preparation process: (1) The negative electrode roll double-layer transfer electrolyte layer process is adopted, and the electrolyte layer winding and unwinding process is realized based on the negative electrode sheet, thereby changing the traditional single-layer stacking all-solid-state battery assembly into a roll-to-roll docking process, thereby greatly improving the assembly efficiency; (2) The surface of the electrolyte membrane is treated to improve the density and adhesion of the electrolyte membrane surface, increase the transfer success rate, and ultimately improve the yield rate of continuous assembly; (3) The double steel belt press process of the composite material industry is introduced, combined with the advantages of the traditional composite flat plate press and roller pressing process, which not only ensures the efficiency of transfer composite but also ensures the yield rate of transfer composite.
[0198] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A solid-state lithium-ion battery, characterized in that: It comprises a positive electrode material belt, an electrolyte membrane and a negative electrode material belt, wherein the positive electrode material belt is bonded to the negative electrode material belt through the electrolyte membrane; an ionic liquid treatment layer is provided between the electrolyte membrane and the positive electrode material belt and the negative electrode material belt; The electrolyte membrane includes a sulfide electrolyte and a binder, wherein the mass proportion of the sulfide electrolyte is 80%-99%; wherein the sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125 At least one of S4 and Li4SnS4; the binder in the electrolyte membrane is selected from at least one of polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, polyvinyl alcohol, acrylates and nitrile-butadiene rubber; The preparation method of the solid-state lithium-ion battery comprises: S1. Prepare a positive electrode material strip, a negative electrode material strip and an electrolyte material strip; the negative electrode material strip comprises a negative electrode current collector and a negative electrode active layer attached to the negative electrode current collector, the positive electrode material strip comprises a positive electrode current collector and a positive electrode active layer attached to the positive electrode current collector; the electrolyte material strip comprises a base film and an electrolyte membrane attached to the base film; S2, transferring the electrolyte material strip onto the negative electrode active layer to make the electrolyte membrane and the negative electrode active layer adhere to each other, and then tearing off the base film; S3, laminating the positive electrode active layer on the positive electrode material strip with the electrolyte membrane laminated on the negative electrode active layer in step S2 to obtain the solid-state lithium-ion battery; Wherein, the preparation method also satisfies: in step S2, before transferring the electrolyte membrane onto the negative electrode active layer, the ionic liquid treatment layer is arranged on the surface of the electrolyte membrane away from the base membrane; and the ionic liquid is deposited on the surface of the electrolyte membrane by vapor deposition to obtain the ionic liquid treatment layer.
2. The solid-state lithium-ion battery according to claim 1, characterized in that: The ionic liquid treatment layer is prepared by depositing an ionic liquid on the surface of the electrolyte membrane.
3. The solid-state lithium-ion battery according to claim 2, characterized in that: The solid-state lithium-ion battery further has at least one of features B to D: B. The ionic liquid used in preparing the ionic liquid treatment layer is selected from at least one of 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium diamine, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium ethyl sulfate, 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate; C. The thickness of the ionic liquid treatment layer is 5nm-1000nm; D. The thickness of the electrolyte membrane is 10 μm-100 μm.
4. The solid-state lithium-ion battery according to claim 1, characterized in that: The negative electrode material strip comprises a negative electrode current collector and a negative electrode active layer; The negative electrode active layer comprises, by mass fraction, 60%-85% of negative electrode active material, 1%-30% of conductive agent, 1%-30% of sulfide electrolyte and 0.1%-10% of binder; The negative electrode material strip further has at least one of features F to J: F. The negative electrode active material is selected from at least one of graphite, lithium titanate, silicon oxygen, silicon carbon and silicon-based alloy; G. The conductive agent is selected from at least one of conductive carbon, acetylene black, vapor-grown carbon fiber and carbon nanotubes; H. The sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125S4 and at least one of Li4SnS4; I. When the negative electrode material strip is made by a dry process, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride binder, acrylic resin, polytetrafluoroethylene and styrene-butadiene rubber; J. When the negative electrode material strip is made by a wet process, the binder is selected from at least one of polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, polyvinyl alcohol, acrylic esters and nitrile-butadiene rubber.
5. The solid-state lithium-ion battery according to claim 1, characterized in that: The size of the positive electrode material strip is smaller than that of the negative electrode material strip; The positive electrode strip comprises a positive electrode current collector and a positive electrode active layer; Wherein, the positive electrode active layer includes 60%-85% of positive electrode active material, 1%-30% of conductive agent, 1%-30% of sulfide electrolyte and 0.1%-10% of binder by mass fraction; The positive electrode material strip further has at least one of features K to O: K, the positive electrode active material is selected from at least one of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, nickel cobalt lithium manganese oxide, high nickel positive electrode material and lithium manganese rich positive electrode material; L, the conductive agent is selected from at least one of carbon black, acetylene black, vapor-grown carbon fiber and carbon nanotubes; M. The sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 3.875 Sn 0.875 As 0.125 At least one of S4 and Li4SnS4; N. When the positive electrode strip is made by a dry process, the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride binder, acrylic resin, polytetrafluoroethylene and styrene-butadiene rubber; O. When the positive electrode material strip is made by a wet process, the binder is selected from at least one of polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, polyvinyl alcohol, acrylic esters and nitrile-butadiene rubber.
6. A method for preparing a solid-state lithium-ion battery as claimed in any one of claims 1 to 5, characterized in that: include: The first negative electrode active layer and the second negative electrode active layer are respectively attached to both sides of the negative electrode current collector, and the first negative electrode active layer and the second negative electrode active layer are both attached to the electrolyte membrane on the side away from the negative electrode current collector; Wherein, in step S1, the positive electrode material strip, the negative electrode material strip and the electrolyte material strip are all in a continuous roll shape, and after the negative electrode material strip and the electrolyte material strip are unwound, the electrolyte material strip is transferred to the negative electrode active layer by pressing; after the positive electrode material strip is unwound, the positive electrode active layer is laminated with the electrolyte membrane laminated on the negative electrode active layer in step S2 by pressing; The pressing comprises at least one of roller pressing, isostatic pressing and flat plate pressing.
7. The preparation method according to claim 6, characterized in that: The formation process of the electrolyte membrane includes: mixing a sulfide electrolyte, a binder and an electrolyte solvent according to the composition of the electrolyte membrane to obtain an electrolyte slurry, applying the electrolyte slurry on one side of the base membrane, and drying to form the electrolyte membrane; wherein the electrolyte solvent is selected from at least one of butyl butyrate, isobutyl isobutyrate, n-hexane, n-heptane, toluene, xylene, anisole, cyclohexanone and 1,3,5-trimethylbenzene; and / or The material of the electrolyte base film is selected from at least one of polyethylene terephthalate, polyamide, polyimide, polypropylene, aluminum foil and stainless steel foil; and / or The formation process of the ionic liquid treatment layer includes: depositing ionic liquid on the electrolyte membrane by vapor deposition to form the ionic liquid treatment layer.
8. The preparation method according to claim 6, characterized in that: The negative electrode material strip is prepared by a dry process or a wet process; When the negative electrode material strip is prepared by a dry process, the preparation process includes: mixing the raw materials at a low speed, shearing at a high speed and hot rolling in sequence according to the composition of the negative electrode active layer to obtain the negative electrode active layer, and laminating the negative electrode active layer to the negative electrode current collector; When the negative electrode material strip is prepared by a wet process, the preparation process includes: mixing various raw materials according to the composition of the negative electrode active layer to form a homogenous slurry, coating the slurry on the negative electrode current collector, and drying the slurry.
9. The preparation method according to claim 6, characterized in that: The positive electrode material strip is cut so that the size of the positive electrode material strip is smaller than the size of the negative electrode material strip, the positive electrode active layer on the positive electrode material strip is laminated with the electrolyte membrane laminated on the negative electrode active layer in step S2, and then cut and stacked to obtain the solid-state lithium-ion battery; The positive electrode material strip is prepared by a dry process or a wet process; When the positive electrode material strip is prepared by a dry process, the preparation process includes: mixing the raw materials at a low speed, shearing at a high speed and hot rolling in sequence according to the composition of the positive electrode active layer to obtain the positive electrode active layer, and laminating the positive electrode active layer to the positive electrode current collector; When the positive electrode material strip is prepared by a wet process, the preparation process includes: mixing various raw materials according to the composition of the positive electrode active layer to form a homogenous slurry, coating the slurry on the positive electrode current collector, and drying the slurry.
Citation Information
Patent Citations
Application of sulfide electrolyte in preparing all-solid-state battery
CN105489931A
Composite electrolyte, preparation method thereof and lithium ion battery
CN115189016A